TINGKAT KEPATUHAN PASIEN HIPERTENSI TERHADAP EDUKASI PENATALAKSANAAN HIPERTENSI OLEH PETUGAS KESEHATAN PUSKESMAS ABANG I, KABUPATEN KARANGASEM BALI PERIODE JANUARI-DESEMBER 2013 - Felix Harianto (DiscoverSys Inc., 2016)
Hypertension is a disease which needs a life time management so that hypertensive patients’ blood pressure can be controlled. As a result, hypertensive patients’ compliance towards hypertensive management advice given to them becomes a crucial thing. A study by Kenny and Karisma in 2013 about hypertensive patients compliance in taking antihypertensive drugs in Denpasar shows only 29% of all samples has a good compliance. This study aims to make an overview of hypertensive patients’ compliance towards medical advice given by medical staff in Abang I health centre, Karangasem district, of January 2013 to December 2013. This is a quantitative descriptive study with a cross sectional approach with 79 samples. The samples are hypertensive patients in Abang I health centre’s working area of January 2013 to December 2013. Data is obtained by a structured interview with questionnaires help. The result of this study shows there are patients that don’t adhere towards medical advice about salt consumption (29,1%), alcohol consumption (10,1%), smoking (21,5%), physical activity (60,8%), medical check-up (32,9%), and pharmacological medication consumption (34,2%).